European Portuguese Accent in Acoustic Models for Non-native English Speakers - Simões, C.; Teixeira, C.; Dias, J.; Daniela Braga; Lopes, A. (Progress in Pattern Recognition, Image Analysis and Applications, Iberoamerican Congress on Pattern Recognition CIARP 2007, 2007)
The development of automatic speech recognition systems poses several known difficulties. One of them concerns the recognizer's accuracy when dealing with non-native speakers of a given language. Normally a recognizer precision is lower for non-native users. Hence our goal is to improve this low accuracy rate when the speech recognition system is confronted with a foreign accent. A typical usage scenario is to apply these models in applications where European Portuguese is dominant but English may also frequently occur. Therefore, several experiments were performed using cross-word triphone-based models, which were then trained with speech corpora containing European Portuguese native speakers, English native speakers and English spoken by European Portuguese native speakers. © Springer-Verlag Berlin Heidelberg 2007.